Cesárea Electiva y su Repercusión en la Respiración Neonatal. Hospital II – 2 - Minsa, 2013” - Dantas Pérez, Teófila Acela (2014)
This research "elective Caesarean section and its impact on neonatal Respiratory Hospital II - 2 - MINSA, 2013, is a quantitative, retroprospectivo, Analytical, cross-sectional study; aimed at determining the impact of elective Cesarean on neonatal respiration. The study population consisted Of 242 patients and 242 cesarean vaginal birth. The results were that the population was characterized as mostly the age Group of 15 to 25 years 38.4% (93) with elective cesarean Section and vaginal delivery in the age group of 26-35 years to 41.7% (101). 40.5% (98) of women with elective cesarean have primary-school Education and 38.4% (93) with vaginal delivery have high school Degree, according to marital status 41.7% (101) of women With cesarean collective or vaginal delivery have free union. As For occupation women with elective caesarean are housewives in 55.4% (134) and equal to those of vaginal delivery with 47.9% (116). Regarding The place of origin women with elective cesarean come from urban areas with 142 (59%) as well as those of vaginal delivery with 188 (78%). The frequency of elective cesarean section in pregnant women treated at The Hospital II - 2 MINSA is 31.0% (650) and the main causes or indication For elective caesarean study population was the iterative section with 29.3% (71) followed by maternal infections in 25.6% (62). In conclusion statistically elective cesarean if impacts on the occurrence of Neonatal respiratory distress syndrome in patients treated in the Hospital II - 2 - MINSA, higher relative risk of 1.0.